SUPERGRAVITY AND NATURE’S GRAND UNIFIED FIELD MODELS - Melibaev Muxtardjan (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION Supergravity and nature’s grand unified field models are considered. Abstract: Supergravity and nature’s grand unified field models are considered.